Ficus insipida tree rings as biomonitors for gaseous elemental mercury in the artisanal gold mining-impacted Peruvian Amazon - Gerson, Jacqueline; Lehnherr, Igor; Luu, Taylor; Bergquist, Bridget; Szponar, Natalie; Fernandez, Luis E.; Vega, Claudia; Porter, Trevor J. (Frontiers in Environmental Science, 2025)
IntroductionThe primary source of anthropogenic atmospheric mercury (Hg) emissions globally is artisanal and small-scale gold mining (ASGM). Estimates of Hg emissions from ASGM are poorly constrained due to a lack of monitoring data and the informal, generally unregulated nature of this industry. Trees accumulate atmospheric gaseous elemental mercury (GEM) in bolewood following stomatal uptake and thus have the potential to be used as biomonitors to quantify the spatial and temporal footprint of Hg emissions from ASGM.MethodsWe collected tree cores from Ficus insipida at three mining-impacted and two remote, unimpacted sites in the Peruvian Amazon (n = 4 trees per site).ResultsWe show that tree ring Hg concentrations were higher near ASGM activity located near mining towns (6.0 ng g−1) compared to remote sites (0.9 ng g−1) and recent tree rings were strongly linearly correlated with atmospheric GEM concentrations across all sites (p < 0.0001, r2 = 0.64), especially in the dry season when there is enhanced ASGM activity (p < 0.0001, r2 = 0.76), highlighting the potential for tree rings to be used as biomonitors for GEM. At the most impacted sites, tree-ring Hg increased over time in response to intensification of ASGM.DiscussionThus far, applications of dendrochemistry to quantify Hg pollution have been largely restricted to coniferous species in temperate regions, but this study shows that tropical species also quantify Hg pollution. We conclude that Ficus insipida is a suitable biomonitor and powerful tool for characterizing the spatial, and potentially temporal footprint of GEM emissions from ASGM in the neotropics.